Escala fenológica, estimativa da área foliar e um método simples e barato para vernalização de statice - Buffon, Paola Ana (2021)
The statice is an important and appreciated cut flower, as its stems have high post-harvest quality, such as which add value and lightness to the floral arrangements. In Brazil, statice crops are concentrated in winter and spring, with the sale of stems on the dead date. The production of statice is easily carried out by small rural producers, since the crop does not need infrastructure, it can be cultivated in the field and has a low implementation cost. Studies involving phenology, growth, development and the requirements of this species are limited or very old. This dissertation has as main objective to contribute to increase the knowledge about the development and growth of the statice in order to assist the rural producers improving the management of this flower culture and consequently to improve the management, productivity and the quality of floral stems of statice. In the years 2019 and 2020, experiments were carried out in the field of transplantation times using assorted statice seeds (mix); an experiment in a protected environment with two cultivars (QIS Purple and QIS Yellow); and an experiment to test periods of vernalization with one cultivar (QIS Yellow). These experiments were carried out at different times, with different cultivars and seed mix to test the hypotheses of this work, put the above objectives into practice and achieve results and responses for rural producers, as well as increasing the knowledge of this flower culture. This was made possible through daily measurements and evaluations and field observations. In view of this, the results achieved enabled the development of a phenological scale for the statice culture with three phases: germination, vegetative and reproductive, which describe the development based on morphological characters and management practices. The determination of an empirical mathematical equation and the shape coefficient to estimate the leaf area of the crop, with the potential equation AF = 0.5996. (CL) the one that best adjusted the data for the statice culture and, finally, the adaptation of a domestic refrigerator in a BOD prototype to vernalize statice seedlings and other propagating materials enabling the production of statice cut flowers in more of a time of year.